UiTM and Al-Azhar University, Gaza sign MoU to facilitate education and research beyond borders / Zakiah Mohd Noordin and Assoc. Prof. Dr. Mahmathi Karuppannan - Mohd Noordin, Zakiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 20th March 2023, Universiti Teknologi MARA (UiTM) and Al-Azhar University, Gaza (AUG) signed a memorandum of understanding (MoU) in various fields focusing on the cooperation and promotion of mutual understanding, academic, cultural and scientific thoughts as well as staff exchanges. The MoU was signed by UiTM Vice-Chancellor, YBhg. Prof. Datuk Ts. Dr. Hajah Roziah Mohd Janor and AUG's Chancellor, Prof. Omar Melad. The signing ceremony was officiated by UiTM Deputy Vice Chancellor (Academic and International), YBhg. Prof. Datin Dr. Suzana Sulaiman and attended by representatives from both institutions including Assistant Professor Mohammed Taha, Dean, Faculty of Pharmacy, AUG and Prof. Dato' Dr. Abu Bakar Abdul Majeed, Dean, Faculty of Pharmacy, UiTM.